The Infinite Learning Chain : Flipped Professional Labs for Learning and Knowledge Co-Creation - Gordillo Martorell, José Antonio; Martin-Torres, Javier; Zorzano Mier, María-Paz; Mathanlal, Thasshwin; Cuartielles, David; Johansson, Mattis (Open Education Studies, 2019)
Nowadays universities and other classical research institutions are changing their role in knowledge creation. In general terms we can characterize this transition as the path from “Closed Science” to “Open Science” as a part of a deeper and structural phenomenon known as “knowledge democratization”, where different stakeholders as students, makers and other tech and science enthusiasts are able to create knowledge learning from the researchers and cooperating with them. In this process, science engagement of these new actors is a key point to stimulate their creativity, get some important research skills learnt directly from the researchers and be able to apply these skills teaching others in a continuous “learning chain”. In this article, we introduce some main features and preliminary results of an experiment called “The infinite learning chain” done in cooperation with Arduino, focused on sensing science and based in a real research project of Group of Atmospheric Science (GAS) called Luleå Environmental Monitoring Stations (LEMS). We debate some interesting questions related to the impact of the format in terms of science engagement, STEM skills acquisition and cooperative learning involvement. We used as “learning ecosystem” a professional Lab, the INSPIRE Lab a complete multidisciplinary facility for space and environmental research and exploration